2022
DOI: 10.1149/1945-7111/ac735b
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Corrosion Studies in Molten Chloride Salts

Abstract: This study investigates corrosion of Fe-(Cr)-Ni model alloys in eutectic molten chloride salt mixtures that broadly simulate the heat transfer circuits of molten salt cooled nuclear reactors. The primary focus is impurity-driven corrosion and selective dissolution of electrochemically reactive element(s) (dealloying), which are known degradation modes for Fe- and Ni-based alloys in molten salts. This study demonstrates that a Mg rod performs close to a true Mg|Mg2+ reference electrode system in a MgCl2 contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 82 publications
(144 reference statements)
0
15
0
Order By: Relevance
“…Electrochemical measurement of the moisture content supported the effectiveness of this purification procedure and was previously described in Ref. 51.…”
Section: Experimental Methodsmentioning
confidence: 94%
See 2 more Smart Citations
“…Electrochemical measurement of the moisture content supported the effectiveness of this purification procedure and was previously described in Ref. 51.…”
Section: Experimental Methodsmentioning
confidence: 94%
“…A schematic of the experimental setup and a detailed procedure was previously described. 51 The working electrode is the alloy of interest (see Materials and sample preparation section), and graphite was used as the counter electrode. Mg was used as a true Mg|Mg 2+ reference electrode (RE) for this study and was found to have a fast and stable potential in molten Cl salts when MgCl 2 was one of the constituents, which was ensured by calibration against "dynamic" Mg REs.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…31-19.04 µg•m −3 in winter and 4.28-9.17 µg•m −3 in summer [17]. The Cl − penetrates the surface of the metal material into the substrate, causing the metal to undergo electrochemical corrosion and form unstable iron chloride compounds [18], and Cl − is absorbent and more likely to form an electrolyte of chloride, which is more aggressive toward metals [19]. Pitting occurs in metal under the Cl − corrosion environment, which can develop into cracks at low cyclic stress (well below the fatigue limit of pure mechanical fatigue), which eventually leads to the metal cracking and failing [20].…”
Section: Introductionmentioning
confidence: 99%
“…As an alternative approach, molten salt has been demonstrated as a promising dealloying agent to fabricate porous structures 26,27 . Molten salt dealloying (MSD) was motivated by the salt-induced corrosive attack of metals and alloys in next-generation nuclear reactor system 28 , concentrated solar power plants [29][30][31] , and waste incineration plants 32,33 .…”
mentioning
confidence: 99%